The Effects of Sampling Frequency and Questionnaire Length on Perceived Burden, Compliance, and Careless Responding in Experience Sampling Data in a Student Population. (March 2022) - Eisele, Gudrun; Vachon, Hugo; Lafit, Ginette; Kuppens, Peter; Houben, Marlies; Myin-Germeys, Inez; Viechtbauer, Wolfgang
Currently, little is known about the association between assessment intensity, burden, data quantity, and data quality in experience sampling method (ESM) studies. Researchers therefore have insufficient information to make informed decisions about the design of their ESM study. Our aim was to investigate the effects of different sampling frequencies and questionnaire lengths on burden, compliance, and careless responding. Students ( n = 163) received either a 30- or 60-item questionnaire three, six, or nine times per day for 14 days. Preregistered multilevel regression analyses and analyses of variance were used to analyze the effect of design condition on momentary outcomes, changes in those outcomes over time, and retrospective outcomes. Our findings offer support for increased burden and compromised data quantity and quality with longer questionnaires, but not with increased sampling frequency. We therefore advise against the use of long ESM questionnaires, while high-sampling frequencies do not seem to be associated with negative consequences.